Suárez et Berkeley (1685−1753). Les limites de l’obéissance. Résistance du pouvoir, résistance au pouvoir, résistance par le pouvoir - Coujou, Jean-Paul (Anales del Seminario de Historia de la Filosofía, 2022)
This article analyzes the confrontation between the work of Suarez and that of Berkeley. Suarez is a representative of the Jesuit current of the Counter Reformation engaged in a polemic with James I of England over the foundation and legitimacy of divine right power in the Defensio fidei catholicae adversus de anglicana secta. The theory of Berkeley, an orthodox and conservative Anglican bishop who deals with passive obedience faithful to the Pauline imperative according to which «he who resists civil authority resists the order that God has established» is developed in On Passive Obedience. Such a confrontation allows us to reformulate the question of the basis of consent to the law, as well as that of the limits that correspond or not to being reasonable and free, to be able to apply it. The comparison is made from the analysis of 1) The limits of the power transferred by the political community to the sovereign; 2) the conditions for disobedience and 3) the ontological necessity of resistance